IMPLEMENTASI KEBIJAKAN BAWASLU DALAM MELAKSANAKAN FUNGSI PENGAWASAN UJARAN KEBENCIAN DI MEDIA SOSIAL : Studi Kasus Pada Pilkada DKI Jakarta Tahun 2017 - Rifqi Naufal Putra (2022)
Hate speech that occurred in the DKI Jakarta Pilkada campaign has become an open secret that the issue is used as a political commodity that is used by each candidate for election needs. This study aims to explain the implementation of the Bawaslu policy in carrying out its supervisory function in cases of hate speech on social media, especially during the 2017 DKI Jakarta Regional Head Election. Data collection was carried out by in-depth interviews and literature studies in order to obtain complex and sensitive explanations. The theory that the author uses as a basis for thinking in analyzing this case is the implementation of the policies written by Grindle. The analysis that the author does emphasizes the context of the pattern of relationships that occur between actors involved in supervision during the 2017 DKI Jakarta Pilkada and its relation to the data findings that the authors get. The results showed that the efforts made by Bawaslu in supervising hate speech cases were promoting socialization with various stakeholders, establishing partnerships with other government agencies, and opening the widest possible reporting channels to the public to report findings of hate speech cases. In addition, there are obstacles for Bawaslu to carry out this, namely the widespread use of anonymous accounts in hate speech on social media, and the polarization of socio-political conditions at that time.